Don Cupitt: theological pioneer? - Graham, Elaine L. (Theology, 2024)
This final article in a three-part series exploring the contemporary significance of the theologian and philosopher of religion Don Cupitt examines the extent to which he might be considered a ‘theological pioneer’. There are three possible areas of innovation: Cupitt’s work on non-realism, his adoption of postmodern philosophy and his advocacy of a religion of everyday speech. In each of these, Cupitt carried out ground-breaking work, but it is less clear whether his ideas have exercised a significant and lasting influence. While the Sea of Faith television series (1984) generated a substantial popular following, his work has not been widely adopted or developed by successive generations of theologians or scholars of religion.